Impact of Ownership Structure on Bank Risk Taking: A Comparative Analysis of Conventional Banks and Islamic Banks of Pakistan - ARIF HUSSAIN; DR. ALAM REHMAN; AQSA SIDDIQUE; HASEEB UR REHMAN (Journal of Business & Tourism, 2021)
This study is about the impact of ownership structure on bank risk taking with comparison between conventional banks and Islamic banks of Pakistan. Z-Score and SDROA are used as risk taking variables. While managerial ownership, institutional ownership, foreign ownership and block holders were taken as proxies for ownership structure. Ten private commercial banks and four Islamic banks were randomly selected and data have been collected from annual reports of these banks from 2010 to 2016. The result suggested that all the proxies of ownership structure i.e. managerial ownership, institutional ownership, foreign ownership and block holders have significant positive impact on Z-Score. On the other hand using SDROA as proxy for risk taking the proxies of managerial ownership has significant positive impact on SDROA and institutional ownership has significant negative impact on SDROA of banks in Pakistan. On the other hand foreign ownership and block holders have insignificant impact on SDROA. The result of BankID is significant which shows that ownership structure has significant impact on bank risk taking in conventional banks while in Islamic banks ownership structure doesn’t have any significant impact on bank risk.